A Pragmatic Analysis of Politeness Strategies Employed by English-Speaking Influencers in Responding to Public Conflicts on Instagram and X - Basma Fathimah Az-Zahra; Nurfithri Nurfithri (Literaturia: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study investigates the politeness strategies employed by English-speaking influencers when responding to public conflicts on Instagram and X. Using a qualitative digital discourse analysis, the study examined 180 public posts and related responses produced by 12 influencers between January 2022 and December 2024. The data were classified according to Brown and Levinson’s framework into positive politeness, negative politeness, off-record, and bald-on-record strategies, while the analysis also considered platform affordances and sociopragmatic factors. The findings show that positive politeness was the most frequently used strategy, accounting for 42.3% of the data, followed by off-record strategies at 28.9%, negative politeness at 18.6%, and bald-on-record strategies at 10.2%. Instagram tended to support more elaborated, emotionally framed, and community-oriented responses, whereas X encouraged more concise, direct, and publicly contested communication. Strategy selection was influenced by social distance, relative power, the seriousness of the conflict, audience expectations, and reputational risk. The study concludes that politeness in influencer conflict responses functions not merely as linguistic courtesy but as a strategic resource for face management, identity negotiation, trust restoration, and digital reputation repair.